Risk factors for Human Immunodeficiency Virus in South-South Nigeria
Background: HIV/AIDS is a global pandemic that has continued to pose a maiorthreatto public health especially in the resource poor regions of the world. The purpose of the study wasto investigate how some factors impact on HIV infection in the south-south geopoliticalzone ofNigeria. Method: The study was carried out using government hospitals in the six states in the zone comprising Edo, Delta, Bayelsa, Rivers, Akwa-ibom and Cross River. The study design was a cross sectional survey and the population were HIV positive and Hlv negative subjects who accessed drugs in the Pharmacy department of the selected hospitals. The main study instrument was a structured questionnaire and purposive sampling was used. A total of 1250 questionnaires were distributed based on subject traffic in each of the hospitals and the distribution was as follows: Edo-450, Delta-300, Bayelsa- 100, Rivers-150, Akwa Ibom-130, Cross River-120. The usable questionnaires returned was 955 (76.4%) and in this order Eclo-415 (92.2%), Delta-249 (83.0%), Bayelsa-69 (69.0%), Rivers-101 (67.3%), Akwa lbom 68(S2.3%